Dyskryminacja instytucjonalna kobiet na polskim rynku pracy - Sielska, Alicja (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article presents the problem of discrimination against women by the state. Based on the economic analysis, the author attempted to demonstrate that the institutional discrimination could cause similar consequences as the tax wedge or the minimum wage, leading to a decrease in women’s employment, their reduced professional activities as well as to a higher unemployment rate. The problem of women’s discrimination was analyzed based on the Polish labor market. For this purpose the author pointed out the gender pay gap in Poland and analyzed the rights granted to women on the labor market in the context of the cost incurred by the employer
Keywords: women discrimination; institutional discrimination; labor market; Poland